Challenges and Opportunities in Stroke Nursing Research: Global Views From a Panel of Nurse Researchers. Issue 3 (June 2022) - Ramazanu, Sheena; Bautista, Cynthia; Green, Theresa; Rhudy, Lori M.; Rogado, Maria Isabelita C.; Baby, Priya; Woon, Caroline; Martinez, Rudolf Cymorr Kirby Palogan; von Gaudecker, Jane R.; Nydahl, Peter; Mbakaya, Balwani Chingatichifwe; Said, Nizar B.; et al.
ABSTRACT: INTRODUCTION: A diverse group of neuroscience nurse experts discussed stroke nursing research at the 5th International Neuroscience Nursing Research Symposium. Panel experts from Singapore, India, Australia, New Zealand, the Philippines, Malawi, Germany, Palestine, Kenya, Japan, and the United States collaborated to examine similarities and differences in nurse-led stroke research conducted in their home countries. This article reflects panel insights on challenges and opportunities for nurse-led stroke research. DISCUSSION: The research challenges discussed include nursing independence, the processes of informed consent and randomization process, obtaining adequate independent funding, recruiting research subjects, and working with vulnerable groups. The major opportunities to leverage and improve stroke nursing research include facilitating the nurse investigator role, information digitalization, improving health literacy, and collaboration between nurse researchers. SUMMARY: We are living in a volatile, uncertain, complex, and ambiguous world, and the COVID-19 pandemic has accentuated many challenges. There is a need to allow for creativity around recruitment and conducting stroke research. The use of technology reduces travel needs and mitigates many safety, financial, and transportation-related problems. Although the pandemic has highlighted the challenges faced when conducting stroke-related research, there are remarkable similarities in opportunities to improve outcomes.